TOXIDADE RESIDUAL DE ACARICIDAS A Euseius citrifolius DENMARK & MUMA, 1970 (ACARI: PHYTOSEIIDADE) EM CITROS - Sato, Mário Eidi; Cerávolo, Leonardo Coutinho; Cezário, Antonio Carlos; Raga, Adalton; Montes, Sonia M. N. M. (REVISTA DE AGRICULTURA, 2015)
TOXIDADE RESIDUAL DE ACARICIDAS A Euseius citrifolius DENMARK & MUMA, 1970 (ACARI: PHYTOSEIIDADE) EM CITROS